Digital Education as an Effort to Improve ARV Adherence Among People Living with HIV AIDS (PWHA) - Maharsi, Eri Dian; Djannatun, Titiek; Maulidyasari, Siti (Jurnal Sehat Indonesia (JUSINDO), 2025)
Background: The discovery of ARVs was a revolution in the treatment of ODHA. The success of HIV/AIDS treatment is determined by adherence to taking ARVs. Non-compliance can be caused by physical discomfort while taking ARVs. Non-compliance can promote HIV resistance. Motivation and knowledge are needed to be compliant with ARV therapy. There needs to be activities to increase the motivation and knowledge of ODHA in consuming ARVs. Objective: To determine the effectiveness of online seminars in increasing the motivation and knowledge of ODHA in consuming ARVs. Method: carried out by holding an online seminar to ODHA and to find out the description of motivation, and knowledge in the use of ARV in ODHA, respondents were given a pretest and posttest. Results: 56 respondents who filled out the pretest and posttest consisted of 60.7% males, 39.3% females, the most ages 53.5% were 30 to 40 years, the most high school education was 57.1%, who used ARV 80.4%; Motivation: The most motivation to consume ARVs comes from Doctors/Nurses/Psychologists/Health Workers at 22%. The most reason was 35.7% to be able to do activities as before. 19.6% of respondents were not motivated and did not use ARVs. Knowledge; 92.9% of respondents had good knowledge and there was no change between pretest and post-test. This can happen because respondents who consume ARVs already have prior knowledge of ARVs. Conclusion: Respondents who consume ARVs are respondents who have good motivation and good knowledge about ARVs. Respondents who did not consume ARVs were unmotivated and partially knowledgeable. Suggestion: Online seminars need to be encouraged to increase and maintain motivation and knowledge in consuming ARVs in ODHA